Penyuluhan Low Back Pain (LBP) Di Posyandu Lansia Ketelan Surakarta - Ferdyan Dimas Mahendra; Wijianto Wijianto; Yusuf Arianto (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Elderly people are susceptible to health problems, one of which is that their joint movement is reduced compared to when they were young. This occurs because the soft tissue in the joint bearing area decreases, which causes the ability of the bones and joints to weaken in supporting the body. One of the problems that many elderly people encounter is low back pain (LBP). LBP is a muscle (musculoskeletal) disorder which can be characterized by pain in the lumbar or lumbo-sacral area. LBP has the highest prevalence globally in musculoskeletal conditions and is the main cause of disability worldwide. The aim of holding this counseling is to increase knowledge about LBP and practice exercises independently at home so as to reduce complaints. The method for this outreach is by means of lectures and distribution of leaflets, evaluation of this activity uses a questionnaire that is distributed after and after the material delivery activity. The results of the counseling showed an increase in posyandu members' understanding of the material that had been presented. With this increased understanding, it is hoped that posyandu members can implement exercises that can reduce complaints of back pain.